Danggui Buxue decoction regulates the immune function and intestinal microbiota of cyclophosphamide induced immunosuppressed mice - Huang, Huan; Xie, Yufei; Li, Xifeng; Gui, Fuxing; Yang, Pingrui; Li, Yutao; Zhang, Li; Du, Hongxu; Bi, Shicheng; Cao, Liting (Frontiers in Pharmacology, 2024)
This study was conducted to investigate the protective effects of Danggui Buxue decoction (DBD) on the immunity, intestinal mucosal barrier function and gut microbiota in cyclophosphamide (CY) induced immunosuppressed (IS) mice. This study takes mice as the research object. A mouse model of IS induced by CY.Pathological examination, ELISA and molecular biology techniques were used to investigate the immunomodulatory effects of DBD. The results showed that DBD alleviated spleen tissue damage and restored impaired immune functions, such as increased thymus index and CD4+/CD8+ subsets of spleen lymphocytes (P < 0.05). In addition, DBD could increase ileum villi length and the ratio of villi length to crypt depth (V/C), and decrease crypt depth (P < 0.05). Moreover, DBD administration upregulated the expression of ZO-1, Occludin, Claudin-1, MUC-2 mRNA in ileum (P < 0.05). And the secretions of sIgA and ZO-1 in ileum were also significantly improved (P < 0.05). Furthermore, the administration of DBD can increase the diversity of gut microbiota, improve the composition of intestinal flora and increase the relative abundance of beneficial genus, such as Bacteroides. In conclusion, our study indicates that DBD has potential application for enhancing immunity.